2022
DOI: 10.37329/cetta.v5i2.1541
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of The Problem-Based Learning Model on The Interest and Learning Outcomes of Mathematics of Elementary School Students

Abstract: This research aims to: 1) know the difference in interest in learning mathematics between students who follow the problem-based learning model with students who follow conventional learning models, 2) know the difference in mathematics learning outcomes between students who follow the problem-based learning model and students who follow conventional learning models, 3) simultaneously know the differences in learning interests and learning outcomes of mathematics between students who follow the problem-based le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Third, the calculation results showed that the students' ability to understand solar system material through the problem-based learning (PBL) learning model and who had a high interest in learning were better than those who were given the problem-based learning (PBL) learning model and had a low interest in learning. This second finding was in line with the findings of Suparya et al (2022)who reported that there was a significant difference between student learning interest and the PBL model on student learning outcomes.…”
Section: Interaction Between Learning Model and Learning Interest On ...supporting
confidence: 89%
“…Third, the calculation results showed that the students' ability to understand solar system material through the problem-based learning (PBL) learning model and who had a high interest in learning were better than those who were given the problem-based learning (PBL) learning model and had a low interest in learning. This second finding was in line with the findings of Suparya et al (2022)who reported that there was a significant difference between student learning interest and the PBL model on student learning outcomes.…”
Section: Interaction Between Learning Model and Learning Interest On ...supporting
confidence: 89%
“…Meanwhile, some studies showed that ICT-based or -assisted mathematics learning had modest positive effect on students' numerical literacy [22, 28, 31, 40-42, 45, 47]. Moreover, a few of studies revealed that ICT-based orassisted mathematics learning had weak positive effect on students' numerical literacy [43,44,46,48,49,73]. Of these reports, it can be stated that there is heterogeneous effect of ICT-based or -assisted mathematics learning on students' numerical literacy.…”
Section: Introductionmentioning
confidence: 99%